p53 and Zinc: A Malleable Relationship - Ha, Jeung-Hoi; Prela, Orjola; Carpizo, Darren R.; Loh, Stewart N. (Frontiers in Molecular Biosciences, 2022)
A large percentage of transcription factors require zinc to bind DNA. In this review, we discuss what makes p53 unique among zinc-dependent transcription factors. The conformation of p53 is unusually malleable: p53 binds zinc extremely tightly when folded, but is intrinsically unstable in the absence of zinc at 37 °C. Whether the wild-type protein folds in the cell is largely determined by the concentration of available zinc. Consequently, zinc dysregulation in the cell as well as a large percentage of tumorigenic p53 mutations can cause p53 to lose zinc, misfold, and forfeit its tumor suppressing activity. We highlight p53's noteworthy biophysical properties that give rise to its malleability and how proper zinc binding can be restored by synthetic metallochaperones to reactivate mutant p53. The activity and mechanism of metallochaperones are compared to those of other mutant p53-targeted drugs with an emphasis on those that have reached the clinical trial stage.